Extended Spectrum β-Lactamase–producing Escherichia coli in Neonatal Care Unit - Sarah Tschudin-Sutter; Reno Frei; Manuel Battegay; Irene Hoesli; Andreas F. Widmer (Emerging Infectious Diseases, 2010)
An outbreak of extended-spectrum β-lactamase–producing Escherichia coli in a neonatal care unit began with transmission from a mother to her newborn twins during vaginal delivery. Subsequently, infection spread by healthcare worker contact with other neonates; a healthcare worker also was infected. Knowledge about transmission may improve infection control measures.